Ethan Hom. Book Review “Evicted” by Matthew Desmond : Ethan Hom. Book Review "Evicted" by Matthew Desmond - Hom, Ethan (Young Scholars Grinchenko – Seton International Journal, 2022)
Ethan Hom. Book Review “Evicted” by Matthew Desmond